VO#001 Approval of unit rates for additional steel work for SF01-15 as non-schedule item - Brac University (Brac University, 2023)
This record consists of general correspondence regarding approval of unit rates for additional steel work for SF01-15 as non-schedule item of BRACU new campus project.